Public relations in ecuador: Exploratory and descriptive research about career development - Yaguache Quichimbo, J. (2017)
In this digital era, the efforts of the organizations to design a symmetrical and bidirectional model of relation and interest management with the public require the projection of a certain image and prestige as a result of the strategic planning of communication. However, this systemic perspective, where communication becomes a key cross-cutting theme along the organizational process, and which assigns the communication professional an executive role Dircom, is not a fixed element on the reality of Ecuadorian companies. This work is the result of research carried out by the Observatorio de la Comunicación Estratégica del Ecuador of the Universidad Técnica Particular de Loja, set up in 2013 to explore the professional profile of business communicators (Dircom).